Analysis of Marketing Mix Characteristics of Marketing Factor 7P (Product, Price, Place, Promotion, People, Process, Physical Building) to Patient Satisfaction of Inpatient Patient Hospital Muhammadiyah Ahmad Dahlan Kediri City - Tety Yuliantine; Indasah Indasah; Sandu Siyoto (Journal for Quality in Public Health, 2018)
Hospital marketing mix is a group of variables tht can be controlled and used the hospital to influence the reaction of the users of services.The aim of the study is to analize the effect of marketing mix 7P(product, price, place, promotion, process, people, physical building) on patient satisfaction in inpatient hospital of Muhammadiyah Ahmad Dahlan Kediri City. The type of this research is quantitative research with analytic observational research design with cross sectional approach. The study was conducted on October until December 31, 2017 at Muhammadiyah Ahmad Dahlan Hospital Kediri City with 600 inpatient patients as the population. The sample size is 240 respondents. Data were collected using questionnaires. Data were multiple linear regression test with α = 0,05. The results showed that the most of the respondents are female (53,3%), between ages 20-35 years (52,1%) educated high school eqivalent (39,6%), working private (34,6%), pay with BPJS (76,25%), stay in class III (56,7%). The analysis indicated that F-test = 90,484 sig.0,000, t test = 6,579 sig 0,000, R2=73,2. there is a influence of product (p=0,000), price (p=0,000), place(p=0,000), promotion (p=0,000), process (p=0,000), people (p=0,000), physical building (p=0,000) have effect of patient satisfaction. The most influential variable is physical building (β=0,442). Marketing mix has asignificant effect on patient satisfaction of inpatient hospital of Muhammadiyah. Suggested to the hospital to further improve the marketing mix strategies of the hospital so that patient satisfaction can be achieved.